Analisis Faktor Yang Berhubungan Dengan Hipertensi Pada Remaja - Suryawan, Zahrotul Fitria (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: Hypertension is the cardiovascular disease that contribute to at least 45% of deaths from heart disease, and 51% of deaths from stroke. Adolescents with high blood pressure have a high risk of becoming hypertensive during adulthood. Objective: This study was aimed to investigate factors correlating with hypertension in adolescent. Methods: This study design was correlational with cross-sectional approach. The number of respondents was 125 people selected by simple random sampling technique. The independent variable of this research is gender, family history, BMI (Body Mass Index), sodium intake, smoking, psychogenic stress, parental income, and physical activity. The dependent variable of this research is hypertension. Data were taken through questionnaires, measurement of blood pressure, weight, and height and data analyzed using Spearman Correlation and Chi-Square test with Î±